The Influence of Sustainability Report Disclosure on The Performance of Banking Companies Listed on The Indonesia Stock Exchange - Djupiansyah Ganie; Siti Munawaroh; Sayugo Adi Purwanto; Desi Putri Febrianti; Caetano Carceres Correia (Pusat Riset dan Inovasi Nasional, 2025)
Based on the results of the study, it can be seen that the disclosure of sustainability reports on the economic aspect does not have a positive and significant effect on company performance as proxied by ROA, while on DAR it has a negative and significant effect. On the environmental aspect, it has a positive and significant effect on company performance as proxied by ROA but on DAR it has no effect. And on the social aspect, ROA has a negative and significant effect while on DAR it has a positive and significant effect.